Changes in the oral mucosa and general indicators with COVID 19 (SARS-CoV-2): a single-center descriptive study - Z. S. Khabadze; K. E. Sobolev; I. M. Todua; O. S. Mordanov (Эндодонтия Today, 2020)
Aim. To study the state of oral mucosa and rationale of Its changes In patients with a laboratory-con^rmed diagnosis of SARS-CoV-2, moderate severity.Materials and methods. A retrospective single-center study was conducted on patients who were In the Infectious diseases department from May to June 2020 with an Initial diagnosis of ICD-X: J18.9: coronavirus Infection. This study Included 90 patients aged 24 to 83years (52 male and 38 female, average age 53.6 ± 9.7years).Results. C-reactIve protein was Increased In 81 Individuals upon admission (44.15 ± 31.8 mg /dl). Twenty patients had Increased tibrinogen values (average Increased tibrinogen values were 5.96 ± 1.6 g /1). The analysis for D-dImer was held In 15 patients (average value 348 ± 103.68 ng/ml), 10 people from that with the increased indicators (435 ± 24 ng / ml). Hemorrhagic manifestations occurred in 12 (13.3%) patients, whose history was not burdened. Pronounced xeroderma of the facial region and angular cheilitis were detected in 21 (23.3%) patients. In 80 patients (88.8%), an examination of the mucous membrane of the tongue was observed plaque from white, lightyellowto brown. In 36(40%) patients, pigmentation was detected in the area of the attached gingiva on the upper and lower jaws.Conclusions. With COVID 19 (SARS-CoV-2), changes in oral mucosa are not the primary cause, but appear as a result of drug treatment and disease progression, despite the fact that the oral cavity is one of the sources of entry gates for infection.